2020
DOI: 10.1103/physreva.101.032113
|View full text |Cite
|
Sign up to set email alerts
|

Counterintuitive role of geometry in transport by quantum walks

Abstract: Quantum walks are accepted as a generic model for quantum transport. The character of the transport crucially depends on the properties of the walk like its geometry and the driving coin. We demonstrate that increasing transport distance between source and target or adding redundant branches to the actual graph may surprisingly result in a significant enhancement of transport efficiency. We explain analytically the observed non-classical effects using the concept of trapped states for several intriguing geomet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 40 publications
5
30
0
Order By: Relevance
“…These are the eigenstates of the unitary evolution operator which do not have a support on the sinks. Trapped states crucially affect the efficiency of quantum transport [8] and lead to counter-intuitive effects, e.g., the transport efficiency can be improved by increasing the distance between the initial vertex and the sink [9,10]. We find a similar phenomena to this quantum walk model in the experiment on the energy transfer of the dressed photon [11] through the nanoparticles distributed in a finite threedimensional grid [12].…”
Section: Introductionsupporting
confidence: 56%
“…These are the eigenstates of the unitary evolution operator which do not have a support on the sinks. Trapped states crucially affect the efficiency of quantum transport [8] and lead to counter-intuitive effects, e.g., the transport efficiency can be improved by increasing the distance between the initial vertex and the sink [9,10]. We find a similar phenomena to this quantum walk model in the experiment on the energy transfer of the dressed photon [11] through the nanoparticles distributed in a finite threedimensional grid [12].…”
Section: Introductionsupporting
confidence: 56%
“…Trapped states crucially affect the efficiency of quantum transport [8] and lead to counter-intuitive effects, e.g. the transport efficiency can be improved by increasing the distance between the initial vertex and the sink [9,10]. We find a similar phenomena to this quantum walk model in the experiment on the energy transfer of the dressed photon [11] through the nanoparticles distributed in a finite three dimensional grid [12].…”
Section: Introductionsupporting
confidence: 57%
“…Recently, it was shown how the underlying geometry of Grover PCQW controls the structure of walker's trapped states [33]. The detailed analytical recipe for constructing the basis has essentially contributed to identify interesting counterintuitive quantum transport phenomena [34]. In particular, study-ing Grover PCQWs on the ladder graph and Cayley trees demonstrated that by increasing the transport distance or adding redundant blind branches one can eventually enhance excitation source-to-sink quantum transport.…”
mentioning
confidence: 99%